Experimental and Modeling of Solubility of Sitagliptin Phosphate, in Supercritical Carbon Dioxide: Proposing a New Association Model - Rojas-Sepulveda, A (Nature Research, 2023)
The solubility of an anti-hyperglycemic agent drug, (R)-4-oxo-4-[3-(trifluoromethyl)-5,6-dihydro [1,2,4] triazolo[4,3-a] pyrazin-7(8H)-yl]-1-(2,4,5-trifluorophenyl) butan-2-amine (also known as Sitagliptin phosphate) in supercritical carbon dioxide (scCO2) was determined by ananalytical and dynamic technique at different temperatures (308, 318, 328 and 338 K) and pressure (12–30 MPa) values. The measured solubilities were in the range of 3.02 × 10–5 to 5.17 × 10–5, 2.71 × 10–5 to 5.83 × 10–5, 2.39 × 10–5 to 6.51 × 10–5 and 2.07 × 10–5 to 6.98 × 10−5 in mole fraction at (308, 318, 328 and 338) K, respectively. The solubility data were correlated with existing density models and with a new association model. © 2023, Springer Nature Limited.